Bio-socio-economic analysis of ESBN fishery of Kattoli coastal area of Chattogram, Bangladesh (Asian Journal of Medical and Biological Research, 2023)
In consideration of the characteristics inherent to the estuarine ecosystem, the employment of the estuarine set bag net (ESBN) emerges as an effective instrument for the capture of a diverse spectrum of finfish and shellfish species. The present investigation, conducted between May and December 2015 in Kattoli, a representative locality along the Chattogram coast, was undertaken to perform a comprehensive bio-socio-economic analysis of the ESBN fishery. The analysis of the catch composition in Kattoli revealed that finfish constituted 67.67%, shrimp accounted for 24.34%, and crab made up 7.99% of the total catch. The average daily catch per boat in Kattoli was determined to be 25.8 kg. The zenith of the total daily catch per boat, reaching 70 kg, was observed in December, while the nadir occurred in August, when no fishing activities were recorded in Kattoli. The cumulative catch over the study period in Kattoli amounted to 26,664 kg, with a complete absence of fishing in August. Moreover, the average daily catch per fisherman stood at 6.19 kg in Kattoli. In terms of economic considerations, the mean monthly cost per boat in the Kattoli region was approximately 8,750 BDT, while the average monthly sales revenue exceeded 28,695 BDT in Kattoli. Notably, during July and August, a substantial proportion of fishermen were engaged in Hilsa (Tenualosa ilisha) fishing utilizing gill nets, which resulted in a diminished catch with ESBN during these months. Furthermore, the preliminary socio-economic conditions of the study area were also explored. This research offers valuable insights into the bio-socio-economic dimensions of the ESBN fishery in the Kattoli coastal area, with potential practical implications for fisheries management and the livelihoods of the local fishing community.Asian J. Med. Biol. Res. 2023, 9 (4), 114-125